Development of a theoretical framework based on the MAPR model for stage-based, individualized mobile smoking cessation interventions through systematic literature review and expert consultation - Shuilian CHU; Hang JING; Lirong LIANG; Jun LI (Zhongguo gonggong weisheng)
ObjectiveTo develop a theoretical framework for stage-based, individualized mobile smoking cessation interventions to guide the design of smoking cessation applications (APPs). MethodsA systematic literature review of studies of smoking cessation APPs was conducted from December 2023 to January 2024. Classic behavior change theories applied in existing smoking cessation APPs were adapted through literature review and expert consultation to establish a motivation-ability-prompt-reflect/reward (MAPR) model. Based on the established MAPR model, theoretical framework for a stage-based, individualized mobile smoking cessation interventions was constructed. Using the constructed theoretical framework, two experts classified intervention strategies within the functional modules of two smoking cessation APPs, and a consistency ratio was calculated to assess the reliability of the framework. ResultsThe theoretical framework constructed is divided into three layers. The first layer includes five core intervention elements: motivation, capability, prompting, reflection, and reward. The second layer defines five stages of cessation experienced by smokers: contemplation, preparation, action, maintenance, and relapse. The third layer consists of nine intervention strategies that can induce behavioral change in smoking cessation: empathy, education, training, incentives, environmental restructuring, modeling, reminders, feedback, and resources and tools that can be used interchangeably across the five stages of smoking cessation. The agreement rates of the intervention strategy classification for two smoking cessation APPs were 88% and 90%, respectively. ConclusionThe stage-based, individualized mobile smoking cessation intervention framework developed in this study provides a concise theoretical framework for the development of professional smoking cessation APPs.